2016
DOI: 10.1186/s12966-016-0446-y
|View full text |Cite
|
Sign up to set email alerts
|

Learning cooking skills at different ages: a cross-sectional study

Abstract: BackgroundCooking skills are increasingly included in strategies to prevent and reduce chronic diet-related diseases and obesity. While cooking interventions target all age groups (Child, Teen and Adult), the optimal age for learning these skills on: 1) skills retention, 2) cooking practices, 3) cooking attitudes, 4) diet quality and 5) health is unknown. Similarly, although the source of learning cooking skills has been previously studied, the differences in learning from these different sources has not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
108
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(137 citation statements)
references
References 47 publications
4
108
1
7
Order By: Relevance
“…This is the largest study showing the strongest single predictor of food skills in young adults is meal preparation as a teenager. This confirms others' conclusions about the importance of learning cooking/food skills early [8,11]. Similarly, university students who participated regularly in food-related activities in their parental home described themselves as having a high level of food literacy [3,7].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This is the largest study showing the strongest single predictor of food skills in young adults is meal preparation as a teenager. This confirms others' conclusions about the importance of learning cooking/food skills early [8,11]. Similarly, university students who participated regularly in food-related activities in their parental home described themselves as having a high level of food literacy [3,7].…”
Section: Discussionsupporting
confidence: 83%
“…Having a parent who modelled food preparation was a motivator for some university students to engage in home food preparation [7]. Practicing food-related skills as a teenager has also been associated with self-reported cooking skills as an adult [8]. Furthermore, university students who have taken a food and nutrition (FN) course were significantly more likely to report increased self-efficacy for food skills [2] and higher intentions toward, and greater confidence in, eating healthfully, especially when under stress [9].…”
Section: Introductionmentioning
confidence: 99%
“…36 The acquisition of basic cooking skills during childhood, adolescence, and young adulthood has been associated with a dietary pattern more closely aligned with the Dietary Guidelines for Americans including an increase in fruit and vegetable consumption. 7,[36][37][38] Additionally, research has shown that although engaging adolescents in food preparation increased interest in cooking and continued use of these skills, engaging young adults in food preparation had a lasting impact on healthy eating habits by increasing fruit and vegetable intake and consistent breakfast and lunch consumption, while decreasing fast food consumption. 39 Another study found that if adults reported adequate cooking skills in young adulthood, they were more likely to prepare meals with vegetables most days, identify as the usual food preparer in the household, eat 3 or more servings of vegetables per day, and consume fast food less frequently.…”
Section: Cooking Skills and Diet Qualitymentioning
confidence: 99%
“…5,6 In a recent study, the mother was reported as the most common source of learning cooking skills (60.1%) followed by sources such as a different relative at home (16.2%), friends (13.6%), and post-primary school (9.3%). 7 Since domestic cooks such as mothers, family members, and friends are becoming less skilled and cooking classes continue to disappear from schools, the number of young adults able to cook for themselves will continue to decline. As young people transition from adolescence to adulthood, they are becoming less equipped to prepare nutritious foods at home.…”
Section: Introductionmentioning
confidence: 99%
“…Assim, recomenda-se que abordagens futuras considerem outras barreiras para o consumo alimentar saudável (MCGOWAN et al, 2017), dentre elas, outros obstáculos do cozinhar em casa, como o uso do tempo, as preferências familiares e a opção pela conveniência no preparo das refeições (BRASIL, 2014a;LAVELLE et al, 2016b).…”
Section: Discussionunclassified